Worship in Medieval England - Salisbury, Matthew Cheung (Past imperfect (ARC Humanities Press), 2018)
The study of medieval liturgy can tell us a great deal not only about the worship of the church, but also about the people who practised it. However, existing scholarship can be problematic and difficult to use. This short book aims to unsettle the notion that liturgiology is a mysterious, abstruse, and monolithic discipline. It challenges some scholarly orthodoxies, hints at the complexity of the liturgy and shows that it needs to be examined in new and different ways.